Adaptation of the Emotional Social Screening Tool for School Readiness (E3SR-R) for Preschoolers: Translation, Equivalence, and Validation Study in Indonesian - Puan Maharani; Devi Lusiria (Da'wa Faculty of Islamic State University Salatiga, 2026)
The Emotional Social Screening Tool for School Readiness (E3SR-R) is a screening instrument designed to assess emotional-social competence as a domain of school readiness. This study aimed to adapt the E3SR-R into Indonesian and to establish preliminary evidence of translation quality, linguistic equivalence, and content validity for use in the Indonesian context. Guided by the International Test Commission guidelines and the adaptation procedures proposed by Sousa and Rojjanasrirat (2011), the study was conducted in two main phases: translation and evaluative review. Assessment of translation quality and linguistic equivalence using the Quality of Translation and Linguistic Equivalence Checklist (QTLC), and estimation of inter-rater reliability using Cohen’s Kappa. The result found that the Indonesian version of the E3SR-R was produced through a systematic and methodologically defensible adaptation process and demonstrated preliminary evidence of linguistic adequacy and content representativeness.